Bioformulation of Bacillus proteolyticus MITWPUB1 and its biosurfactant to control the growth of phytopathogen Sclerotium rolfsii for the crop Brassica juncea var local, as a sustainable approach - Mukadam, Humaira; Gaikwad, Shikha V.; Kutty, Nithya N.; Gaikwad, Vikrant D. (Frontiers in Bioengineering and Biotechnology, 2024)
Bacillus proteolyticus MITWPUB1 is a potential producer of biosurfactants (BSs), and the organism is also found to be a producer of plant growth promoting traits, such as hydrogen cyanide and indole acetic acid (IAA), and a solubilizer of phosphate. The BSs were reportedly a blend of two classes, namely glycolipids and lipopeptides, as found by thin layer chromatography and Fourier-transform infrared spectroscopy analysis. Furthermore, semi-targeted metabolite profiling via liquid chromatography mass spectroscopy revealed the presence of phospholipids, lipopeptides, polyamines, IAA derivatives, and carotenoids. The BS showed dose-dependent antagonistic activity against Sclerotium rolfsii; scanning electron microscopy showed the effects of the BS on S. rolfsii in terms of mycelial deformations and reduced branching patterns. In vitro studies showed that the application of B. proteolyticus MITWPUB1 and its biosurfactant to seeds of Brassica juncea var local enhanced the seed germination rate. However, sawdust-carrier-based bioformulation with B. proteolyticus MITWPUB1 and its BS showed increased growth parameters for B. juncea var L. This study highlights a unique bioformulation combination that controls the growth of the phytopathogen S. rolfsii and enhances the plant growth of B. juncea var L. Bacillus proteolyticus MITWPUB1 was also shown for the first time to be a prominent BS producer with the ability to control the growth of the phytopathogen S. rolfsii.